2015
DOI: 10.1021/ja511802c
|View full text |Cite
|
Sign up to set email alerts
|

Low-Molecular-Weight Carbon Nitrides for Solar Hydrogen Evolution

Abstract: This work focuses on the control of the polymerization process for melon ("graphitic carbon nitride"), with the aim of improving its photocatalytic activity intrinsically. We demonstrate here that reduction of the synthesis temperature leads to a mixture of the monomer melem and its higher condensates. We show that this mixture can be separated and provide evidence that the higher condensates are isolated oligomers of melem. On evaluating their photocatalytic activity for hydrogen evolution, the oligomers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
325
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(348 citation statements)
references
References 80 publications
21
325
2
Order By: Relevance
“…It was recently reported that melon derivatives such as dimelem and trimelem, are capable of visible light absorption. 30 This result contrasts with a subsequent study, which claimed that dimelem and trimelem are unable to absorb visible light. 31 Additionally, a reduced optical gap of PCN at 1.90 eV was reported for an amorphous PCN.…”
Section: Refining the Methodologymentioning
confidence: 65%
See 1 more Smart Citation
“…It was recently reported that melon derivatives such as dimelem and trimelem, are capable of visible light absorption. 30 This result contrasts with a subsequent study, which claimed that dimelem and trimelem are unable to absorb visible light. 31 Additionally, a reduced optical gap of PCN at 1.90 eV was reported for an amorphous PCN.…”
Section: Refining the Methodologymentioning
confidence: 65%
“…The precursor, melamine, was loaded on a lidded alumina boat and heated to different temperatures from room temperature with a ramp rate of 2.2 • C/min in a quartz tube (2.5 cm in diameter) with flowing N 2 gas at a flow rate of 100 mL/min and then held at the desired temperature for 4 h. Essentially, this method using melamine as the precursor compound is inspired by the original synthesis of crystalline melon by Lotsch 15 and subsequent syntheses of other crystalline forms of melon 17 and melon derivatives that have particularly interesting optical features. 30 Each sample is labeled as CNX, where X indicates the synthesis temperature. For example, CN500 is the sample produced from melamine by heating at 500 • C for 4 h. For CN390, the material was kept at 390 • C for 24 h and the resultant white solid (∼5 g) was boiled in 100 ml water with 10 vol% acetic acid.…”
Section: Syntheses Of Pcnsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Polymeric carbon nitride (CN), initially reported by Berzelius and Liebig in 1834, has been found to be a stable organic photocatalyst for the photoredox splitting of water (half-reactions with suitable sacrificial reagents). 13,14 The basic sub-unit would be either triazine or heptazine or even both interconnected through NH-bridges, resulting from the polycondensation of precursors such as dicyandiamide, cyanuric acid, melamine, and urea, with continuous elimination of NH 3 . 15,16 However, theoretical quantum chemical calculations have shown that structures containing heptazine motifs are thermodynamically more stable than those based on triazine units.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] The idealized structure of g-C3N4 is not realized when using the most common synthetic procedures involving hydrogen-containing precursors. [18,[20][21][22][23][24][25][26] Synthesis is typically achieved via thermal decomposition of molecular precursors such as cyanamide, dicyanamide, melamine or urea. For example cyanamide (1) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[25] In contrast, low molecular weight melem oligomers prepared under an inert atmosphere are up to six times more active than melon analogues. [25] Related high temperature routes between 520 -640 o C gave materials with superior photoactivity, attributed to the distribution of imino/amino defects [87] and range of oligomerization. Postsynthetic modification can also alter defect concentration.…”
mentioning
confidence: 99%